Zinc Phthalocyanine Labelled Polyethylene Glycol: Preparation, Characterization, Interaction with Bovine Serum Albumin and Near Infrared Fluorescence Imaging in Vivo - Tianjun Liu; Bo Cao; Feng Lv; Yanli Cui (Molecules, 2012)
Zinc phthalocyanine labelled polyethylene glycol was prepared to track and monitor the in vivo fate of polyethylene glycol. The chemical structures were characterized by nuclear magnetic resonance and infrared spectroscopy. Their light stability and fluorescence quantum yield were evaluated by UV-Visible and fluorescence spectroscopy methods. The interaction of zinc phthalocyanine labelled polyethylene glycol with bovine serum albumin was evaluated by fluorescence titration and isothermal titration calorimetry methods. Optical imaging in vivo, organ aggregation as well as distribution of fluorescence experiments for tracking polyethylene glycol were performed with zinc phthalocyanine labelled polyethylene glycol as fluorescent agent. Results show that zinc phthalocyanine labelled polyethylene glycol has good optical stability and high emission ability in the near infrared region. Imaging results demonstrate that zinc phthalocyanine labelled polyethylene glycol can track and monitor the in vivo process by near infrared fluorescence imaging, which implies its potential in biomaterials evaluation in vivo by a real-time noninvasive method.